Analisis Pengaruh Keputusan Penggunaan Telemedicine Halodoc di Kota Bogor - Farah Fauziah Rahmasari; Putri Asmita Wigati; Rani Tiyas Budiyanti (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The number of visits to telemedicine applications has increased during the Covid-19 pandemic. Halodoc is the most commonly used telemedicine platform in Indonesia. The return of public activity to health services after the easing of the pandemic were a challenge and opportunity for telemedicine service providers. Marketing is an important factor in influencing people's decision to use a product/services. This study aimed to examine the effect of Marketing 4.0 strategies on the usage of Halodoc's telemedicine services in Bogor City. The study used a quantitative method with a cross sectional approach, total research sample are 270 respondents who used Halodoc's telemedicine services, accidental sampling are used to select participants for the study, and the questionnaire had been tested for validity and reliability. The collected data was analyzed using the logistic regression test. The results showed that Co-creation strategy (Sig.=0.016) and Conversation strategy (Sig.=0.028) had an effect on the usage of telemedicine services through the Halodoc application in Bogor City, while Currency (Sig.=0.216) and Communal Activation strategy (Sig.=0.152) did not. The researchers recommend Halodoc to evaluate, improve, and develop an effective and sustainable marketing strategies to increase the use of telemedicine services in Bogor City.